Pembatalan Hibah Orang Tua Kepada Anak di Pengadilan Agama - Rania Areta Nur Annisa (CV Rewang Rencang, 2024)
Gifts (hibah) are generally irrevocable. However, Islamic law provides exceptions that allow parents to revoke gifts given to their children. In the case of West Jakarta Religious Court Decision No. 946/Pdt.G/2024/PA.JB, the plaintiff granted a gift to their child without the consent of their spouse and other children, leading to family conflict. The research shows that the gift was declared null and void as it violated Article 36 of the Marriage Law and Article 210 of the Compilation of Islamic Law, which regulate consent in the use of joint property and the maximum limit for gifts. The judge ordered the return of the gift but did not grant the request for a security seizure. This case highlights the importance of caution in the implementation of gifts and the enforcement of justice principles in resolving family disputes.